1998
DOI: 10.1103/physrevb.57.14344
|View full text |Cite
|
Sign up to set email alerts
|

Electron-spin-resonance investigation of the heavy-fermion compoundCe(Cu1xNix

Abstract: The heavy-fermion compound Ce(Cu 1Ϫx Ni x ) 2 Ge 2 is investigated by Gd 3ϩ electron spin resonance ͑ESR͒ within the whole concentration range (0рxр1). The Kondo-lattice system exhibits an alloying-induced transition from an antiferromagnetically ordered heavy-fermion ground state (xϭ0) to pure Kondo-like behavior with strongly enhanced effective masses (xϭ1). The temperature dependence of the ESR linewidth ⌬H allows one to distinguish between the different ground states. The nature of the magnetic order chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The analysis of the spectra following ref. [11] results in low values for the uniaxial CEF-parameter 0.3 GHz < ∼ b 0 2 < ∼ 0.7 GHz, compared to the microwave frequency ν = 9 GHz. Hence, the influence of the crystal field can be neglected for all further discussion.…”
Section: A Esr Spectramentioning
confidence: 87%
See 2 more Smart Citations
“…The analysis of the spectra following ref. [11] results in low values for the uniaxial CEF-parameter 0.3 GHz < ∼ b 0 2 < ∼ 0.7 GHz, compared to the microwave frequency ν = 9 GHz. Hence, the influence of the crystal field can be neglected for all further discussion.…”
Section: A Esr Spectramentioning
confidence: 87%
“…If the exchange interaction is large compared to the crystal-field splitting, the different dipolar transitions are strongly coupled to each other, and the spectrum is exchange narrowed into a single ESR line with orientation dependent linewidth and resonance field. For a closer discussion of these effects refer to [11]. The spectra of all samples show only a weak dependence on the orientation.…”
Section: A Esr Spectramentioning
confidence: 96%
See 1 more Smart Citation
“…However, the temperature evolution of the linewidth observed in Gd 1−x Sr x TiO 3 differs completely from the linear Korringa law [12], but it reveals similar features as the Gd ESR [11,13] and NMR spin-lattice relaxation rate [14] [4]. In all these systems a second important contribution to the spin-lattice relaxation arises from spin fluctuations of the electronic bath due to the fluctuation-dissipation theorem, which for temperatures large compared to the exciting frequency k B T ≫hω reads…”
mentioning
confidence: 87%
“…The evaluation of comparable Gd 3+ spectra has been described in detail in a previous publication [11]. Their intensity follows the CurieWeiss behavior of the static susceptibility measured with the SQUID magnetometer and comparison with a standard sample showed that it is due to all Gd 3+ spins.…”
mentioning
confidence: 99%